Pendampingan Pastoral Holistik: Sebuah Usulan Konseptual Pembinaan Warga Gereja - Fibry Jati Nugroho (Sekolah Tinggi Teologi Simpson, 2017)
Fibry Jati Nugroho, Pastoral Assistance Holistic: A Proposed Conceptual Development Residents Church. A strong church is formed of a strong congregation. Strong congregation obtained from the pastoral care that actively touches the whole life of the churches. The Church should strive to develop a holistic pastoral care to the congregation. Various programs designed to be used to achieve a holistic pastoral care. Multiculture congregation accompanied by multiproblem, requiring pastoral agents set the strategy and create a model to be able to provide a holistic pastoral care services to the citizens of his church. The concept of holistic pastoral care of Howard Clinebell and Totok Wiryasaputra will help create a framework to analyze the development of church people holistically. The theoretical framework will be integrated with pastoral models developed by David Yonggi Cho's Yoido Full Gospel Church. The concept and model of pastoral care holistic support each other as well as a